PERAN GURU DALAM MENGATASI KETIDAKDISIPLINAN PESERTA DIDIK PADA PROSES PEMBELAJARAN IPAS KELAS IV MADRASAH IBTIDAIYAH NEGERI DONGGALA - Amalia Syahida; Muhammad Djamil M. Nur; Andi Suktomansya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the factors causing student indiscipline and the role of teachers in addressing it during the Natural and Social Sciences (IPAS) learning process in the fourth grade at Madrasah Ibtidaiyah Negeri (MIN) Donggala. This research employed a qualitative approach with a descriptive method. Data collection techniques included observation, interviews, and documentation. The results show that the main factors contributing to student indiscipline are lack of learning motivation, monotonous teaching methods, insufficient teacher firmness, and negative peer influence. To address these issues, the teacher plays a crucial role as a classroom manager. The teacher implements several strategies, such as providing positive feedback in the form of recognition or rewards for well-behaved students, applying varied and engaging teaching methods, giving warnings or consequences to students who break rules.